2008
DOI: 10.1097/phm.0b013e31817c115b
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Multilevel Chemical Denervation Procedures Using Phenol or Botulinum Toxin or Both in a Pediatric Population

Abstract: Although these procedures are not without adverse effects, this series suggests that the potential benefits outweigh the risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…The overall incidence of UEs in this study was higher (21%) than in previous studies with the same combinedagent treatment (about 7%) [15,16]. However, the findings may not be comparable because of a difference in the data retrieval criteria.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The overall incidence of UEs in this study was higher (21%) than in previous studies with the same combinedagent treatment (about 7%) [15,16]. However, the findings may not be comparable because of a difference in the data retrieval criteria.…”
Section: Discussioncontrasting
confidence: 82%
“…Soreness at injection sites could be from a mechanical effect of the needle [22], in addition to stinging pain from phenol because of its nature as an astringent. Kolaski et al [16] reported similar resultsdthat is, tenderness, bruising, and swelling occurred more frequently in sites injected with phenol compared with BTX-A. Adhesive bandages were applied over the phenol injection sites as landmarks so the caregivers could apply ice compression to decrease the pain.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Uptake of the toxin into the nerve terminal over the next several days results in a pre-synaptic blockade at the neuromuscular junction, resulting in decrease in tone (Koman 2000). The effects of phenol and botulinum toxin are temporary, and although the injections are technically easy, the drugs are potentially fatal and must be administered by a physician well trained in the indications and proper dosing techniques for the drug (Kolaski et al 2008;Koman et al 2003).…”
Section: Management Of Increased Tonementioning
confidence: 99%